Auxin‐based herbicide program for weed control in auxin resistant soybean. Issue 4 (17th October 2022) - Amajioyi, Joy; Nleya, Thandiwe; Reicks, Graig; Moriles‐Miller, Janet; Clay, David; Clay, Sharon
Abstract: Soybean [ Glycine max (L.) Merr.] cultivars resistant to synthetic auxin herbicides have provided another mode of action for the postemergence broadleaf weed control. This field study was conducted at three South Dakota locations [Northeast, NERF; east‐central, ARF; and Southeast, SERF) in 2019 and two locations (ARF and SERF) in 2020. The Enlist E3 and Roundup Ready 2 Xtend cultivars were planted at three dates (early, mid‐, and late season) to examine weed control, agronomic characteristics, nodulation, and yield. Preemergence (PRE) treatment was flumioxazin + metribuzin + S‐metolachlor + glyphosate + pendimethalin. Two postemergence (POST) treatments, based on cultivar, were compared with PRE‐only. The PRE‐only treatment had numerous grasses {including green foxtail [ Setaria viridis (L.) P. Beauv.] and yellow foxtail [ S. pumila (Poir.) Roem. & Schult.], volunteer corn ( Zea mays L.), barnyard grass [ Echinochola crus‐galli (L.) Beauv.], large crabgrass [ Digitaria sanguinalis (L.) Scop.], woolly cupgrass [ Eriochloa villosa (Thunb.) Kunth]} and broadleaf weeds (including redroot pigweed [ Amaranthus retroflexus L.], common lambsquarters [ Chenopodium album L.], waterhemp [ Amaranthus rudis Sauer]) with high density and biomass. POST treatments controlled most of the broadleaf species, although some grasses remained. Yields were similar within a location and year, although differences occurred among planting dates. In 2019, planting date did not influence final yield at ARF (average yield 3, 084 kg ha −1 ). Yield was greatest for the early (NERF) and mid‐planting dates (NERF and SERF) compared with late‐season planting. In 2020, dry conditions occurred, and yields at ARF and SERF were lowest for the late‐season plantings (ranging from 37 to 73% lower depending on cultivar) compared with the early season planting. In 2020, dicamba + glyphosate treatment of the Xtend cultivar had 10% (ARF) and 20% (SERF) greater yield than the acifluorfen + clethodim treatment. Core Ideas: Auxin‐resistant soybean cultivars planted at three locations and dates had similar yields within a location. Preemergence‐only treatments had several grass and broadleaf weeds and high weed biomass. Pretreatments followed by postemergence treatments had fewer weed species and lower weed biomass. Soybean nodulation was influenced by planting date and weed presence but not by herbicide treatment.